PENGGUNAAN MEDIA RODA PINTAR TERHADAP HASIL BELAJAR MENULISAKSARA JAWASISWA - Sa’adah, Kiki lailatus; Basir, Udjang Pairin M.; Susilo, Claudya Zahrani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
This study aims to determine the effect of the use of smart wheel media on learning outcomes of writing the Javanese alphabet (legena script) grade III students of SDN Sengon II Jombang. The results of this study are expected to provide thoughts that can be used as a source of information to increase knowledge, and are used as input and consideration for institutions involved in learning Javanese used as literature for further research. The design of this study was preexperimental and the design used was one group pretest-posttest design. the student were first given a preset question to find out how much the student’s ability before being given the treatment. then student are given posttest questions to determine the effect of the treatment that has been given. Research subjects in grade III students of SDN Sengon II Jombang in the academic year 2019/2020 on oven semester . Data collection techniques using the test. The research was conducted in the even semester of February-April.this research variable is using independent variable and dependedt variables the research insrumen used were: tes sheets, questionnaire sheets, observations sheets and interviem sheets. Students are given tests before and after learning using the smart wheel media in learning to write the Javanese alphabet (legena script), from the pretest and posttest tests that have been obtained the average results of pretest 66 with 17 students getting grades below KKM and 8 students getting grades below KKM, while the average posttest is 91.6 there are no students who score below the KKM. The positive response data from the student questionnaire results was 67.2%. The results showed that the use of smart wheel media in learning Javanese could have a positive influence on student learning outcomes and interest in learning.